2019
DOI: 10.1080/15476286.2019.1657352
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-142-3p suppresses endometriosis by regulating KLF9-mediated autophagy in vitro and in vivo

Abstract: The detailed pathogenesis of endometriosis remains largely unclear despite decades of research. Recent studies have demonstrated that miRNAs plays an important role in endometriosis. The expression of miR-142-3p was decreased in ectopic endometrial tissues, while KLF9 and VEGFA expression levels were increased. Overexpression of miR-142-3p or knockdown of KLF9 significantly suppressed CRL-7566 cell proliferation and metastasis, induced cell apoptosis, and decreased both cell autophagy and vascularization. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 54 publications
3
25
0
Order By: Relevance
“…The described effects of miR-142-3p might be similar across more cell types, as our laboratory has previously shown that miR-142-3p also decreases cell area and migration in breast cancer cell lines [22]. Similar effects of miR-142-3p on migration in endometrial stromal cells were previously observed by Ma and colleagues [2], who attributed these observations to the miR-142-3p effect on KLF9 and VEGFA expression. However, none of our used databases predicted KLF9 as a miR-142-3p Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 17 July 2020 doi:10.20944/preprints202007.0399.v1…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The described effects of miR-142-3p might be similar across more cell types, as our laboratory has previously shown that miR-142-3p also decreases cell area and migration in breast cancer cell lines [22]. Similar effects of miR-142-3p on migration in endometrial stromal cells were previously observed by Ma and colleagues [2], who attributed these observations to the miR-142-3p effect on KLF9 and VEGFA expression. However, none of our used databases predicted KLF9 as a miR-142-3p Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 17 July 2020 doi:10.20944/preprints202007.0399.v1…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, additional targets may have contributed to the functional impact of this miRNA in our functional assay. Finally, wound healing studies in miR-142-3p mice [23] and retroviral delivery studies in an in vivo model of endometriosis [2] suggest that confirmation of our findings in more complex in vivo models of endometriosis may be worthwhile.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…For example, Jia et al reported that miR-17-5p, miR-20a and miR-22 are downregulated in plasma samples from patients with Ems, and investigated their prognostic value (20). Ma et al observed that injection of miR-142-3p significantly attenuated ectopic endometriotic lesions in vivo (34). Li et al also found that miR-451a inhibition reduced established Ems lesions in a murine model (35).…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to several factors, including altered microRNA expression and its associated post-transcriptional regulation of microRNA targets in the ectopic milieu [ 16 , 17 , 18 ]. One microRNA gene that is downregulated at ectopic locations and might thus contribute to these phenotypic changes is the microRNA-142-3p [ 5 , 19 ]. Two previous studies on the endometriotic cell line Hs832.Tc (ATCC CRL-7566) [ 19 ] and the endometrial stroma cell line ST-T1b [ 20 ] identified the transcriptional regulator KLF9 , the interleukin-6 receptor subunit IL6ST /gp130, and steroid sulfatase ( STS ) as regulatory targets of miR-142-3p, however, the exact role microRNA-142-3p plays in the pathophysiology of endometriosis currently remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%